Improvement of Apraxia With Augmented Reality: Influencing Pantomime of Tool Use via Holographic Cues - Rohrbach, Nina; Krewer, Carmen; Löhnert, Lisa; Thierfelder, Annika; Randerath, Jennifer; Jahn, Klaus; Hermsdörfer, Joachim (Frontiers in Neurology, 2021)
Background: Defective pantomime of tool use is a hall mark of limb apraxia. Contextual information has been demonstrated to improve tool use performance. Further, knowledge about the potential impact of technological aids such as augmented reality for patients with limb apraxia is still scarce. Objective: Since augmented reality offers a new way to provide contextual information, we applied it to pantomime of tool use. We hypothesize that the disturbed movement execution can be mitigated by holographic stimulation. If visual stimuli facilitate the access to the appropriate motor program in patients with apraxia, their performance should improve with increased saliency, i.e., should be better when supported by dynamic and holographic cues versus static and screen-based cues. Methods: 21 stroke patients and 23 healthy control subjects were randomized to mime the use of five objects, presented in two Environments (Screen vs. Head Mounted Display, HMD) and two Modes (Static vs. Dynamic) resulting in four conditions (ScreenStat, ScreenDyn, HMDStat, HMDDyn), followed by a real tool demonstration. Pantomiming was analysed by a scoring system using video recordings. Additionally, the sense of presence was assessed using a questionnaire. Results: Healthy control participants performed close to ceiling and significantly better than patients. Patients achieved significantly higher scores with holographic or dynamic cues. Remarkably, when their performance was supported by animated holographic cues (e.g., striking hammer), it did not differ significantly from real tool demonstration. As the sense of presence increases with animated holograms, so does the pantomiming. Conclusion: Patients´ performance improved with visual stimuli of increasing saliency. Future assistive technology could be implemented upon this knowledge and thus, positively impact the rehabilitation process and a patient’s autonomy.